FORMATION OF A HIGH LEVEL OF STUDENT READINESS TO CREATIVE ACTIVITY (Pedagogy of Higher and Secondary Education, 2009)
Some principal approaches to forming a high level of students' readiness for creative activities are viewed in the article. The author focuses on the conception of the term formation of readiness, and proposes a number of the main criteria and indicators for the formation of a high level of students readiness for creative activities.